Extreme states of matter on Earth and in the Cosmos - Fortov, Vladimir E. (The Frontiers collection, 2011)
With its many beautiful colour pictures, this book gives fascinating insights into the unusual forms and behaviour of matter under extremely high pressures and temperatures. These extreme states are generated, among other things, by strong shock, detonation and electric explosion waves, dense laser beams,electron and ion beams, hypersonic entry of spacecraft into dense atmospheres of planets, and in many other situations characterized by extremely high pressures and temperatures. Written by one of the world's foremost experts on the topic, this book will inform and fascinate all scientists dealing with materials properties and physics, and also serve as an excellent introduction to plasma, shock-wave and high-energy-density physics for students and newcomers seeking an overview.